MEDICAL STUDENT’S MENTAL HEALTH: COPING STRATEGIES THAT WORK (AND DON’T) - Widyadhana, Amanda; Rochmanti, Maftuchah (Lux Mensana: Journal of Scientific Health, 2025)
Introduction. Stress, anxiety, and depression are common forms of mental health disorders faced by medical students worldwide. These disorders can lead to depression, anxiety, burnout as well as suicidal ideation and attempts. Coping strategies can help students face psychological distress, either through problem-focused coping, emotion-focused coping, or dysfunctional coping. This review aims to provide the prevalence of stress, anxiety, and depression in medical students, along with effective coping strategies to combat these mental health conditions. Method. This review utilized Google Scholar, PubMed, and Scopus to review articles in English and Indonesian. Various keywords were used, such as "Medical students", "Stress", "Anxiety", "Depression", "Coping", "Coping strategy", "Mahasiswa kedokteran", "Stres", "Ansietas", "Kecemasan", "Depresi", "Koping", and "Strategi koping." The initial search identified 394 articles, of which 34 met the inclusion criteria and were included in this review.  Result & Analysis. Varying reports were found regarding the prevalence of stress, anxiety, and depression among medical students. Students who used problem-focused coping showed correlations with lower levels of stress, anxiety, and depression. Dysfunctional coping has a positive correlation with stress, anxiety, and depression. Some claim that emotion-focused coping is found to be correlated with lower levels of stress, anxiety, and depression. On the contrary, several studies found otherwise. Varying factors lead to stress, anxiety, and depression in medical students. Discussion. Different coping strategies yield different results in relation to stress, anxiety, and depression. This proves the need to encourage healthy coping strategies in medical students to combat mental health disorders.